Muertos incómodos, a very different novel - Méndez González, María Oliva (2019)
The founding violence in Latin America continues to generate fictional storiesthat make visible phenomena associated with national intrahistories, immersedin an inexhaustible cycle of neo-colonialism and struggles for liberation. Thefiliation of Muertos incòmodos to the narrative of the testimony and to thehistorical novel is recorded through the discursive hybridization, the hypertextualityand the juxtaposition of subjectivities that provide a fragmented visionof Mexico in the context of globalization and zapatista autonomy..